Prevalence of self medication practice among students of a medical college (Bangladesh Medical Journal Khulna, 2020)
Background: The unsolicited practice for self medication is commonly seen all over the world. In our country it is also commonly practiced even by health care professionals.Objectives: This study is done to focus on the prevalence and other associated factors in various aspects of self medication among medical students. Methods: This was a descriptive study conducted within 4th year students among 113 participants by using a researcher made questionnaire in Gazi Medical College, Khulna from January 2019 to June 2019. Data analysis was done by using Microsoft excel.Results: The prevalence of self medication was reported at 88.49%. The most important reasons for self medication was previous experiences with the illness (48%), minor illness (30%), and time saving (25%). The greatest number of students used self medication to treat headache (30%), gastric acidity (28%), fever (22%), and runny nose (14%). The data reveals that the highest proportion (38%) of students learned medications from old prescription of doctor provided to cure their past illness. The respondents used different group of drugs where greatest number (32%) used analgesics followed by anti ulcerants (28%), antipyretics (25%), and antibiotics (22%).Conclusion: Due to high prevalence of self medication, it is necessary to implement strict rules and regulations to prevent this practice and provide adequate facilities to access medical services properly.Bang Med J (Khulna) 2019; 52 : 21-24